Beispiel Nr: 51
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y= 3x^2+4x-6\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y= 3x^2+4x-6\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=3x^2+4x-6 \\ y=3(x^2+1\frac{1}{3}x-2) \\ y=3(x^2+1\frac{1}{3}x+\left(\frac{2}{3}\right)^2-\left(\frac{2}{3}\right)^2-2) \\ y=3[(x+\frac{2}{3})^2-\left(\frac{2}{3}\right)^2-2] \\ y=3[(x+\frac{2}{3})^2-\frac{4}{9}-2] \\ y=3[(x+\frac{2}{3})^2-2\frac{4}{9}] \\ y=3(x+\frac{2}{3})^2-7\frac{1}{3} \\ Scheitel(-\frac{2}{3}/-7\frac{1}{3}) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=3x^2+4x-6 \\ y=3(x^2+1\frac{1}{3}x)-6 \\ y=3(x^2+1\frac{1}{3}x+\left(\frac{2}{3}\right)^2-\left(\frac{2}{3}\right)^2)-6 \\ y=3[(x+\frac{2}{3})^2-\left(\frac{2}{3}\right)^2]-6 \\ y=3[(x+\frac{2}{3})^2-\frac{4}{9}]-6 \\ y=3(x+\frac{2}{3})^2-1\frac{1}{3}-6 \\ y=3(x+\frac{2}{3})^2-7\frac{1}{3} \\ Scheitel(-\frac{2}{3}/-7\frac{1}{3}) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=3x^2+4x-6 \\ xs=-\frac{4}{2\cdot 3} \\ xs=-\frac{2}{3} \\ ys=-6-\frac{4^2}{4\cdot3} \\ ys=-7\frac{1}{3} \\ Scheitel(-\frac{2}{3}/-7\frac{1}{3})\\ y=3(x+\frac{2}{3})^2-7\frac{1}{3} \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = [(-7\frac{1}{3});\infty[ \\ \\=3(x+2,23)(x-0,897)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y= 3x^2+4x-6 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 3x^{2}+4x-6 =0 \\ x_{1/2}=\displaystyle\frac{-4 \pm\sqrt{4^{2}-4\cdot 3 \cdot \left(-6\right)}}{2\cdot3} \\ x_{1/2}=\displaystyle \frac{-4 \pm\sqrt{88}}{6} \\ x_{1/2}=\displaystyle \frac{-4 \pm9,38}{6} \\ x_{1}=\displaystyle \frac{-4 +9,38}{6} \qquad x_{2}=\displaystyle \frac{-4 -9,38}{6} \\ x_{1}=0,897 \qquad x_{2}=-2,23 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ 3x^{2}+4x-6 =0 \qquad /:3 \\ x^{2}+1\frac{1}{3}x-2 =0 \\ x_{1/2}=\displaystyle -\frac{1\frac{1}{3}}{2}\pm\sqrt{\left(\frac{1\frac{1}{3}}{2}\right)^2- \left(-2\right)} \\ x_{1/2}=\displaystyle -\frac{2}{3}\pm\sqrt{2\frac{4}{9}} \\ x_{1/2}=\displaystyle -\frac{2}{3}\pm1,56 \\ x_{1}=0,897 \qquad x_{2}=-2,23 \end{array}\\ \end{array}\\ \underline{x_1=-2,23; \quad1\text{-fache Nullstelle}} \\\underline{x_2=0,897; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-2,23&< x <&0,897&< x\\ \hline f(x)&+&0&-&0&+\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-\infty;-2,23[\quad \cup \quad]0,897;\infty[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-2,23;0,897[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$